Age structure and crime rates: The conflicting evidence - Marvell, Thomas B. (Journal of quantitative criminology, 1991)
Because arrest rates are especially high for teenagers and young adults, criminologists have long contended that age structure changes affect crime trends. In recent years, however, this belief has been drawn into question because crime has not declined even though high-crime age groups have shrunk. We argue that the age/crime relationship is probably exaggerated because the high arrest rates for younger persons are due partly to their lesser ability to escape arrest, younger persons commit more group crime, and the age structure of victims should be taken into account. We then review 90 studies that regress crime rates on age structure; only a small minority consistently finds significant relationships. Because of methodological problems in this research, one cannot conclude that the age/crime relationship does not exist, but the weight of evidence shows that forecasts based on demographic trends are not likely to be helpful.